Review of rural settlement research based on bibliometric analysis - Li, Junfang; Song, Wei (Frontiers in Environmental Science, 2023)
Rural settlements are important rural land use types, and rural transformation and reconstruction are global issues in the process of urbanization. Research on rural settlements has been performed form different perspectives. In this paper, we took articles on rural settlements published in the core collection of Web of Science from 1973 to 2021 as the object of measurement analysis. Literature induction was used to determine the research progress, using the Bibliometrix measurement software. We also summarized the number of published papers, authors, research institutions and cooperative relationships, and keywords and investigated the theme evolution in the field of rural settlements. The following main results were obtained: (1) the number of articles related to rural settlements published was 1,703; the time from 1973 to 2021 can be roughly divided into three evolutionary stages: the initial stage (1973–1990), the development stage (1991–2010), and the high-yield stage (2011–2021). The number of articles published increased sharply after 2011, indicating that this research field received increased attention. (2) China and the United States published the largest number of articles in this field, followed by Australia. (3) In recent years, "Immigration", urbanization", "Land use", and “Floating population" were the most frequent keywords. Clustering analysis revealed four research. (4) Research in rural settlement areas changed largely over time; currently, in the context of urbanization, scientists focus on the renovation of rural settlements.